Strengthening the Regional Investment Climate Through Bandung City Regional Regulation Number 4 of 2022: Legal Certainty, Incentives, and Ease of Doing Business - Heigel Parodi Ritonga; Putra Dirgantara; Rifaldo Aditya (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Bandung City Regional Regulation Number 4 of 2022 concerning Investment Implementation serves as a regional legal engineering instrument in response to the shift in national regulatory paradigm following the enactment of the Job Creation Law. This regulation is intended not only as a legal umbrella for investment but also as a framework for driving the regional economy by strengthening legal certainty, ease of doing business, and integrating investment policies with the development direction of Bandung City. This regulation emphasizes the implementation of investment that aligns with riskbased business licensing, spatial planning, infrastructure provision, employment, environmental protection, and strengthening the capacity of the regional bureaucracy. The essence of the regulation positions investment not merely as an influx of capital, but as a regional development ecosystem that includes social and sustainable dimensions, including through partnerships with MSMEs/cooperatives, local labor absorption, and encouragement of the implementation of environmentally friendly technologies. This study aims to analyze how Bandung City Regional Regulation Number 4 of 2022 functions as a legal umbrella and framework for driving the regional investment climate; examine the harmonization of regional economic growth targets with aspects of social openness through strengthening MSME/cooperative partnerships and providing local employment; and examine the relationship between incentive schemes and investment facilitation with control mechanisms as a form of accountability for investment implementation. The research method used is a normative juridical approach withstatute approach, which focuses on analyzing legal documents through a review of the main norms in Regional Regulation 4/2022, including the objectives of the regulation, regional government authority, investment planning in the form of RUPMK and investment potential maps, investor rights and obligations, business sector regulations, incentives and facilities, as well as guidance, supervision, reporting, and administrative sanctions instruments. Normatively, Bandung City Regulation Number 4 of 2022 positions Bandung City not only as a capital destination, but also as an investment ecosystem with legal certainty, oriented towards inclusive, competitive, and sustainable regional economic growth, through partnerships with MSMEs/cooperatives, absorption of local labor, and compliance with environmentally friendly principles that are accountably controlled by the local government.